How Agriculture will Address the Rio+20 Challenges - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Live from Agriculture and Rural Development Day at Rio+20, 18 June 2012 http://www.agricultureday.org Speakers: - Marcelo Bezerra Crivella, Minister of Fisheries and Aquaculture, Brazil - Kanayo F. Nwanze, President, International Fund for Agricultural Development (IFAD) - Roberto Rodrigues, Coordinator of the Agribusiness Center Getulio Vargas Foundation (FGV), former Minister of Agriculture, Livestock, and Supply, Brazil - Jan L. McAlpine, Director, United Nations Forum on Forests Secretariat - Anne Grethe Dalane, Regional Director of Latin America, Yara International - Dyborn Chibonga, Chief Executive Officer, National Smallholder Farmers Association of Malawi (NASFAM) and World Farmers Organisation Chair: Lindiwe Majele Sibanda, Chief Executive Officer and Head of Diplomatic Mission, Food, Agriculture and Natural Resources Policy Analysis Network (FANRPAN) Join the discussion: #rio4ag http://www.twitter.com/agricultureday http://www.facebook.com/agricultureday